Food Integrity and Food Technology Concerns in Canada: Evidence from Two Public Surveys - Ellen Goddard; Violet Muringai; Albert Boaitey (Journal of Food Quality)
Food integrity and food technologies both generate public concerns. There is little research to show the interactions between those concerns in particular samples, especially in Canada. In this paper, data from two national online samples are used to examine an aggregate of food integrity concerns, genetic modification in food, and food nanotechnology concerns in the Canadian public. A variety of trust, health, environmental, and science attitude variables are used to help explain the concerns that vary across the population. In addition, the food integrity concerns are tested as explanatory variables in the technology concern models to establish whether there is a strong or weak link between the two. Tobit and ordered probit regressions are used to model the variables for each of the survey samples. Results are examined to see if they are consistent across surveys and also consistent with an earlier study that was done in Australia. The results suggest that trust in people and trust in a variety of agents within the food system are beliefs that ameliorate concerns about food integrity and the two technologies. However, trust in advocacy organizations appears to be related to higher concerns in each case. Fundamentally and similar to the earlier Australian study, positive scientific attitudes are a major determinant of reduced concerns about food integrity and the two technologies.